Embolism formation and repair of Phyllostachys vivax f. aureocaulis in winter and the role of non-structural carbohydrates in this process - Li, Juan; Wang, Jinge; Chen, Lei; Wu, Chongyang; Li, He; Cheng, Zhanchao; Gao, Jian (Frontiers in Plant Science, 2025)
Phyllostachys vivax f. aureocaulis is an important ornamental plant in Beijing and is primarily cultivated in the Henan, Zhejiang, and Jiangsu provinces of China. Low winter temperatures can lead to xylem embolism and plant mortality; however, there is a scarcity of studies focused on bamboo. Abnormal climatic conditions in Beijing frequently occur during winter, making it essential to investigate changes in the embolism and recovery processes of bamboo in this region. This experiment was conducted from December 2021 to March 2022 to measure the embolization curve and variations in embolization sites across different organs. This study also examined the relationship between hydraulic structural characteristics and embolization regulation by integrating physiological water indices and anatomical modifications. The results revealed that the embolization ratios of the vascular conduits in the culm, twig, and petiole ranged from 99.44% to 54%, 99% to 67%, and 99% to 57%, respectively, from December to March. Vulnerability to culm embolization was greater in January and February than in December and March, with the highest vulnerability observed in February. Non-structural carbohydrates (NSCs) in rhizomes located 15 and 30 cm distance from the culm were significantly higher in March than in December (P< 0.05), accompanied by a significant increase in starch content. The NSC and starch contents in the 10th and 15th culm internodes were significantly elevated in March compared with those in January and February. The net photosynthetic rate was higher in December and March, lower in January and February, and more negative in February. The diameters of the short and long axes of the pit in the duct, the number of parenchyma cell pits, and the area of parenchyma cell pits were significantly reduced in January and February compared with those in December and March (P< 0.05). In December and January, the vascular bundles and cells appeared intact; however, in February, signs of fragmentation and invasion by the filling bodies were observed. By March, the vascular bundles and cells had returned to normal, with a substantial presence of starch granules in the parenchyma cells. These findings provide a basis for introducing bamboo species that can withstand climate change and abnormal winter conditions as well as for implementing effective scientific management strategies.